The Effect of Neutral Electrolyzed Water on the Microbial Population and Quality of Dried Figs (Ficus carica L.) During Storage - Çiğdem Yamaner (Journal of Agricultural Sciences)
Fig is one of economically the most important agricultural products and preserving its quality is of crucial importance. In this study, the efficiency of Neutral Electrolyzed Water (NEW) in the controlling of the microbial load of dried figs was researched. For this reason, it was used three different fig groups. The first group was washed with 10% NEW, the second group was washed with 6% salty water at 50 °C for 1 min, and finally, the third group did not wash as control group. The samples were taken at the beginning of the storage and in monthly periods through 6 months. Initial average amount of mesophilic aerophilic bacteria (MAB) was 3.89 log cfu g-1. This amount was reduced to 0.73 log cfu g-1 after 6 months storage in the group washed with NEW and 2.52 log cfu g-1 in the group washed with salty water. The yeast-mold number was reduced from 3.08 log cfu g-1 to 0.96 log cfu g-1 in the group washed with NEW and 1.9 log cfu g-1 in the group washed with salty water at the end of the 2nd month. It was determined that both applications in comparison with the control group did not cause an important change in physical and chemical parameters such as colour and pH of dried figs. These results show that NEW can be used as a more safe and effective method in reducing the microbial load in comparison with the standard application.